Assessing the perceived influence of religion on brain health among adults in the United Arab Emirates—the Global Brain Health Survey: a cross-sectional study - Elbarazi, Iffat; Abdullahi, Aminu S.; Aziz, Karim Abdel; Stip, Emmanuel; Budin-Ljøsne, Isabelle; Nauman, Javaid (Frontiers in Psychology, 2025)
BackgroundA healthy brain is essential for independent and participatory life. Religion may play a key role in brain health. This study investigated the influence of religion on brain health among adults in the United Arab Emirates (UAE).MethodsThis was a cross-sectional study among adults in the UAE based on the Global Brain Health Survey (GBHS). Information on demographics, knowledge and beliefs about brain health, and religious perceptions and practices related to brain health was collected. Data were summarized using frequencies and percentages. Logistic regression analysis was used to identify factors associated with religious activities and attitudes toward brain health, and results are presented as adjusted odds ratios (OR) and 95% confidence intervals (CI).ResultsA total of 887 participants (65% women) were included. About 78% of women and 73% of men believed that religion strongly influences brain health. About 47% of participants reported frequent practice of religion for their brain health. Frequent thoughts about one’s brain health (OR = 2.52, 95% CI = 1.47–4.31), frequent engagements in religious activities (OR = 33.42, 95% CI = 18.58–60.11), being married (OR = 0.46, 95% CI = 0.23–0.90), and having had COVID-19 (OR = 0.51, 95% CI = 0.27–0.97) were associated with purposeful use of religious activities for brain health.ConclusionOur study found a significant link between religious practices and brain health, suggesting that faith- and spirituality-based approaches may be important for addressing brain health issues. These findings highlight the need for programs that incorporate religious beliefs to improve brain health, offering practical solutions for communities and healthcare providers.